Ulama and Umara in Goverment of Indonesia: A Review Relations of Religion and State - Witro, Doli (Madania: Jurnal Kajian Keislaman, 2020)
Indonesia is well-known as a Muslim majority. However, this does not make Indonesia as an Islamic country. The relationship between religion and state in Islam is fairly interpretive and it nowadays still becomes a debate. The government system applied in this country is democratic. Besides, there has to freedom for the ulama in preaching without being limited by space and time. A number of ulama are currently being persecuted and intimidated that impacts to the lecture to be either stopped, postponed, or even canceled. At this part, the role of the umara (government) is required in enforcing the applicable law and also maintaining security and order in society. This paper aims to highlight the relationship between religion and state in Indonesian by observing the position of the ulama and the role of the umara in terms of Indonesian government. This paper used a qualitative approach to literature research. The data in this study were obtained from library materials. Data analysis methods used in this study were data reduction, data presentation, and conclusion. The results of the analysis showed that in Indonesia there is a separation between religion and state as the secularistic paradigm. However, it is not completely secularistic because in national legal system there is also a transformation of Islamic law. Religious and state affairs are not able to be separated, so are ulama and umara. It is because the state will experience a crisis in religious knowledge without ulama. Otherwise, without umara, religion cannot be implemented correctly within the country. Indonesia merupakan negara yang berpenduduk mayoritas Islam. Namun bukan berarti Indonesia adalah negara Islam. Hubungan agama dan negara dalam Islam cukup banyak penafsiran. Dalam Islam, hal ini masih menjadi perdebatan sampai saat ini. Sistem pemerintahan yang diterapkan di Indonesia saat ini adalah sistem demokrasi. Terlepas dari sistem tersebut, tentu harus memberikan kebebasan para ulama dalam berdakwah tanpa dibatasi oleh ruang dan waktu. Saat ini, ada ulama yang dipersekusi dan diintimidasi sehingga ceramah yang hendak dilaksanakan terpaksa dihentikan, ditunda, bahkan dibatalkan. Disinilah diperlukan peran umara (pemerintah) dalam menegakkan hukum yang berlaku dan juga menjaga keamanan serta ketertiban di masyarakat. Tulisan ini bertujuan menyoroti relasi agama dan negara dalam konteks Indonesia dengan melihat kedudukan ulama dan peran umara dalam pemerintahan Indonesia. Tulisan ini menggunakan metode pendekatan kualitatif yang bersifat penelitian pustaka. Data-data dalam penelitian ini diperoleh dari bahan-bahan yang bersifat pustaka Metode analisis data yang digunakan dalam penelitian ini yaitu reduksi data, penyajian data dan penarikan kesimpulan. Hasil analisis menunjukkan di Indonesia terjadi pemisahan antara agama dan negara sebagaimana paradigma sekuleristik. Tetapi disini tidak sepenuhnya sekularistik karena pada hukum nasional Indonesia juga terjadi transformasi hukum Islam. Urusan agama dan negara tidak dapat dipisahkan. Begitu juga dengan ulama dan umara tidak dapat dipisahkan karena tanpa ulama maka negara akan mengalami krisis ilmu agama dan tanpa umara maka agama tidak bisa diterapkan secara sempurna dalam suatu negara.